Swimming in a crystal. Issue 1 (6th October 2015) - Brown, Aidan T.; Vladescu, Ioana D.; Dawson, Angela; Vissers, Teun; Schwarz-Linek, Jana; Lintuvuori, Juho S.; Poon, Wilson C. K.
Abstract : Colloidal crystals induce orbital motion in self-propelled Janus particles, and destroy orbital motion in E. coli bacteria. Abstract : We study catalytic Janus particles and Escherichia coli bacteria swimming in a two-dimensional colloidal crystal. The Janus particles orbit individual colloids and hop between colloids stochastically, with a hopping rate that varies inversely with fuel (hydrogen peroxide) concentration. At high fuel concentration, these orbits are stable for 100s of revolutions, and the orbital speed oscillates periodically as a result of hydrodynamic, and possibly also phoretic, interactions between the swimmer and the six neighbouring colloids. Motile E. coli bacteria behave very differently in the same colloidal crystal: their circular orbits on plain glass are rectified into long, straight runs, because the bacteria are unable to turn corners inside the crystal.